Visual free recall and recognition in art students and laypeople. - Děchtěrenko, Filip; Bainbridge, Wilma A.; Lukavský, Jiří (Memory & Cognition, 2025)
Artists and laypeople differ in their ability to create drawings. Previous research has shown that artists have improved memory performance during drawing; however, it is unclear whether they have better visual memory after the drawing is finished. In this paper, we focused on the question of differences in visual memory between art students and the general population in two studies. In Study 1, both groups studied a set of images and later drew them in a surprise visual recall test. In Study 2, the drawings from Study 1 were evaluated by a different set of raters based on their drawing quality and similarity to the original image to link drawing evaluations with memory performance for both groups. We found that both groups showed comparable visual recognition memory performance; however, the artist group showed increased recall memory performance. Moreover, they produced drawings that were both better quality and more similar to the original image. Individually, participants whose drawings were rated as better showed higher recognition accuracy. Results from Study 2 also have practical implications for the usage of drawing as a tool for measuring free recall – the majority of the drawings were recognizable, and raters showed a high level of consistency during their evaluation of the drawings. Taken together, we found that artists have better visual recall memory than laypeople.